Pooled Confirmatory Factorial Analysis On Authentic Leadership, Psychological Capital, Job Burnout And Organisational Commitment Based On Primary Healthcare Workers In Sarawak - Ainaa Anum, Araffin Bakar; Noorzilawati, Sahak (MALAYSIAN PUBLIC HEALTH PHYSICIANS’ ASSOCIATION, 2023)
In Structural Equation Modelling, the author steps in the analysis by performing the first step, called Confirmatory Factor Analysis (CFA). It can help researchers avoid erroneous estimations once they try to predict the relevance of a particular factor. It can also be utilised in various scientific areas. Four constructs, including authentic leadership, psychological capital, job burnout and organisational commitment, were assessed simultaneously in a pooled CFA for model fitness based on primary healthcare workers in Sarawak. The compensation of these factors can improve the model's capabilities.